2009
DOI: 10.1634/stemcells.2008-0600
|View full text |Cite
|
Sign up to set email alerts
|

Development of Human Nervous Tissue upon Differentiation of Embryonic Stem Cells in Three-Dimensional Culture

Abstract: Researches on neural differentiation using embryonic stem cells (ESC) require analysis of neurogenesis in conditions mimicking physiological cellular interactions as closely as possible. In this study, we report an air-liquid interface-based culture of human ESC. This culture system allows three-dimensional cell expansion and neural differentiation in the absence of added growth factors. Over a 3-month period, a macroscopically visible, compact tissue developed. Histological coloration revealed a dense neural-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…Normal brain cells were isolated from cortices of Wistar rats and allowed to reaggregate and to mature for 20 days, by placing them on a semi-porous membrane at an air-liquid interface, and subsequently generating characteristic brain HiSpots [220,221]. Histological analysis showed that both neurons and astrocytes were present in these 3D cultures, with a preserved physiological architecture.…”
Section: D Co-cultures Of Tumoral Cns Cells and Normal Brain Cellsmentioning
confidence: 99%
“…Normal brain cells were isolated from cortices of Wistar rats and allowed to reaggregate and to mature for 20 days, by placing them on a semi-porous membrane at an air-liquid interface, and subsequently generating characteristic brain HiSpots [220,221]. Histological analysis showed that both neurons and astrocytes were present in these 3D cultures, with a preserved physiological architecture.…”
Section: D Co-cultures Of Tumoral Cns Cells and Normal Brain Cellsmentioning
confidence: 99%
“…The use of tissue slices from each cellular layer of the cerebellum, placed horizontally, was proposed for the architectural design of the neuronal segment. Only rare cases of human neuronal tissue culture, containing neurons and all necessary kinds of glia cells, are described (Preynat-Seauve et al, 2009). Channels for the growth and proper connection of the axons of the different layers were provided to restore the destroyed interconnections between the layers caused by this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…these do not allow the study of drug transport, but may allow the examination of toxicant effects on the blood-brain barrier structure (Al Ahmad et al, 2011). A variant of the membrane technique is the formation of 3D tissue at an air liquid interphase (DuboisDauphin et al, 2010;Preynat-Seauve et al, 2009). Alternatively, cells may be grown in artificial scaffolds to promote threedimensionality (lu et al, 2012a).…”
Section: Issues and Future Challenges To Be Addressed By 3d In Vitro mentioning
confidence: 99%